2015
DOI: 10.1089/hum.2014.052
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Targeting of Disseminated Liver Tumors Using a Recombinant Adeno-Associated Viral Vector

Abstract: A novel selectively targeting gene delivery approach has been developed for advanced hepatocellular carcinoma (HCC), a leading cause of cancer mortality whose prognosis remains poor. We combine the strong liver tropism of serotype-8 capsid-pseudotyped adeno-associated viral vectors (AAV8) with a liver-specific promoter (HLP) and microRNA-122a (miR-122a)-mediated posttranscriptional regulation. Systemic administration of our AAV8 construct resulted in preferential transduction of the liver and encouragingly of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…GBM8401/ luc2 cells (1 × 10 7 ) in 150 μL mixture containing serum-free RPMI and Matrigel (2:1) were subcutaneously inoculated into the right hind legs of the 30 mice [ 32 ]. We measured the tumor volume of each animal with a digital caliper and calculated with the equation: tumor volume = 0.523 × length × width 2 [ 33 ]. After the tumor volume reached 100–120 mm 3 , mice were randomized into three different treatment groups (n = 10 for each group), including vehicle, PEITC-10 group, and PEITC-20.…”
Section: Methodsmentioning
confidence: 99%
“…GBM8401/ luc2 cells (1 × 10 7 ) in 150 μL mixture containing serum-free RPMI and Matrigel (2:1) were subcutaneously inoculated into the right hind legs of the 30 mice [ 32 ]. We measured the tumor volume of each animal with a digital caliper and calculated with the equation: tumor volume = 0.523 × length × width 2 [ 33 ]. After the tumor volume reached 100–120 mm 3 , mice were randomized into three different treatment groups (n = 10 for each group), including vehicle, PEITC-10 group, and PEITC-20.…”
Section: Methodsmentioning
confidence: 99%
“…Viral vectors with high transfection efficiency are commonly applied for gene delivery. Nevertheless, viral vectors have side effects including immunogenicity, complicated synthesis procedure, and carcinogenicity [ 9 ]. In recent years, nonviral gene vectors with low immunogenicity, simplicity of synthesis, and ease of large-scale production have overcome problems occurring with viral vectors and attracted more attention [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to reports by Peruta et al., who utilized the liver-specific nature of AAV8 to construct miRNA122a-based post-transcriptionally liver detargeted gene delivery system, we observed that transduction of Hepa1-6 with scAAV8-GLuc-miR199a*3 leads to a significant reduction of reporter expression when compared to scAAV8-GLuc. 36 This observation was further corroborated by post-transcriptionally detargeted suicide gene therapy with scAAV8-CD-miR199a*3 in Hepa1-6. Given the ability of AAV8 to transduce liver and tissues of liver origin, our system could provide an option to target disseminated tumors.…”
Section: Discussionmentioning
confidence: 72%